Heutagogy Meets Generative AI in Teacher Education: Examining an Evolving Synergy - Chamo, Nurit; Biberman-Shalev, Liat; Bar-Tal, Smadar; Broza, Orit (Journal of Posthumanism, 2025)
As generative AI (GAI) tools become increasingly embedded in educational contexts, understanding their intersection with learner autonomy is critical—particularly in teacher education. This study explores the evolving synergy between pre-service teachers’ (PSTs) use of GAI tools and their heutagogical orientations, with attention to disciplinary differences. A quantitative analysis was conducted with 181 PSTs (103 from Humanities and 78 from Math and Science), who completed a validated questionnaire based on Blaschke’s four core principles of heutagogy. Results indicate a positive relationship between GAI usage and heutagogical orientation, with Humanities PSTs reporting significantly higher levels of self-regulated and reflective learning principles. While the overall frequency of GAI use did not differ by discipline, its pedagogical implications did: linguistic applications (e.g., writing assistance, translation) were more strongly associated with reflection and metacognition among Humanities students, whereas multimedia-based GAI usage correlated with enhanced problem-solving confidence, reflecting the self-efficacy principle, across both groups. Notably, the cybergogy principle—autonomous learning in digital environments—emerged as most closely linked to GAI engagement, particularly among Humanities participants. Age and program track also influenced outcomes, with younger and secondary-track PSTs demonstrating greater adaptability to digital learning. These findings suggest that while GAI tools are broadly accessible, their transformative potential in teacher education depends on aligning technological integration with disciplinary cultures and learner agency. Fostering this synergy requires teacher education programs to support not only digital fluency but also reflective, self-determined learning across diverse educational contexts.